Three cases of treatment of patients with colonic lipoma - A. A. Kartashev; E. G. Yevtushenko; A. L. Charyshkin (Вестник хирургии имени И.И. Грекова)
Three clinical cases of endoscopic and traditional surgical treatment of patients with a rare pathology – colon lipoma are presented. The diagnosis was established by colonoscopy and biopsy with histological examination. In one observation, the lipoma was removed endoscopically, in two cases, by open surgery. The postoperative period was uneventful, within 12–24 months, there was no recurrence of the disease. The presented cases show the possibility and effectiveness of both endoscopic and open surgical methods for the treatment of patients with colonic lipoma.